The prevalence of premenstrual syndrome in China: a systematic review and meta-analyses - Yang, Yanmei; Jia, Yu; Fu, Songying; Zhang, Lu; Xiang, Feng; Hu, Wanqin; Cao, Xuehua (Frontiers in Psychiatry, 2025)
BackgroundReliable estimates of the prevalence of premenstrual syndrome (PMS) serve as the basis for adequate prevention and treatment. However, the prevalence of PMS has rarely been synthesized at the Chinese level. We conducted this systematic review and meta-analyses to provide accurate and comprehensive evidence on the prevalence of PMS in ChinaMethodsPubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Information, Chinese Scientific Journal (VIP), Wan fang and China Biology Medicine databases were systematically searched from inception until March 8, 2025. The prevalence of PMS in China was analyzed using a random effects model.ResultsA total of 77 studies (108,178 participants) were included in the meta-analyses. The pooled prevalence of PMS in China was 48% (95% CI, 44-53%). Subgroup analyses revealed significant differences in the prevalence of PMS according to the screening tool, region, setting, and mean age. Meta-regression analyses indicated that using a prospective tool was significantly associated with lower prevalence.LimitationsThere was a high degree of heterogeneity among the included studies; The included studies were conducted in urban areas; There was significant publication bias in this meta - analyses; Current meta-analyses contain insufficient information on many risk factors for PMS in China.ConclusionThe findings demonstrate that most Chinese women have PMS. Given the prevalence of PMS in China, future studies should explore its risk and protective factors, provide regular screening, and implement effective preventive and treatment measures for this demographic.